2010
DOI: 10.1242/jeb.039131
|View full text |Cite
|
Sign up to set email alerts
|

To eat or not to eat: the effect of AICAR on food intake regulation in yellow-bellied marmots (Marmota flaviventris)

Abstract: SUMMARYMammals that hibernate (hibernators) exhibit a circannual rhythm of food intake and body mass. In the laboratory during the winter hibernation period, many hibernators enter a series of multi-day torpor bouts, dropping their body temperature to near ambient, and cease to feed even if food is present in their cage. The mechanism(s) that regulates food intake in hibernators is unclear. Recently, AMP-activated protein kinase (AMPK) has been shown to play a key role in the central regulation of food intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…The tissue type, animal species, and duration and depth of hypothermia may contribute to these differences. Interestingly, administration of the somewhat non-selective AMPK activator AICAR into hibernating marmots led to a significant increase in food intake and failure to enter torpor (Florant et al, 2010), suggesting that AMPK may play a role in the metabolic downregulation seen in hibernating species (Drew et al, 2007). A dramatic reduction in pAMPK occurred in stroke mice after hypothermia in our experimental setting.…”
Section: Figmentioning
confidence: 69%
“…The tissue type, animal species, and duration and depth of hypothermia may contribute to these differences. Interestingly, administration of the somewhat non-selective AMPK activator AICAR into hibernating marmots led to a significant increase in food intake and failure to enter torpor (Florant et al, 2010), suggesting that AMPK may play a role in the metabolic downregulation seen in hibernating species (Drew et al, 2007). A dramatic reduction in pAMPK occurred in stroke mice after hypothermia in our experimental setting.…”
Section: Figmentioning
confidence: 69%
“…Thus, the decline in the number of Fos-positive neurons over the active season may result from increased fattening and leptin resistance. Appetite regulation in mammals is a highly complex process, making it likely that other mechanisms contribute to satiation in hibernating species including action of the gut hormones ghrelin and peptide YY, insulin, neuropeptide Y, and hypothalamic AMP kinase [6,8,16,17,19,20,23]. …”
Section: Discussionmentioning
confidence: 99%
“…Information on how AMPK acts in specific areas of the brain, such as hypothalamus, where AMPK acts as a fuel sensor, is lacking in the hibernation literature. Recent experiments by Florant et al (2010) demonstrated that central infusion of the AMPK agonist 5-aminoimidazole-4-carboxamide 1 B-D-ribofuranoside (AICAR) into the third ventricle of winter aphagic marmots caused an initiation of food intake, consistent with AMPK’s role in increasing food intake.…”
Section: Introductionmentioning
confidence: 89%